?NUTRITIONAL QUALITIES OF SMOKED SHRIMP FROM THE SUNDARBANS MANGROVE AREA, BANGLADESH - Hoqa, M Enamul; Islam, M Nazrul; Kamal, M (Biological Sciences - PJSIR, 2003)
Quality aspects of a traditional smoked product from the shrimp Metapenaeus brevicornis in the Sundarbans mangrove area have been discussed. Studies on the physical properties, proximate composition, mineral content and amino acid value show that the quality of traditional smoked product is quite good. During 90 days of storage period the product was found to lose its characteristic properties and overall acceptability. However, smoked shrimp retained its overall acceptability up to 60 days of storage.